A 43Ca nuclear magnetic resonance perspective on octacalcium phosphate and its hybrid derivatives. (4th April 2021) - Laurencin, Danielle; Li, Yang; Duer, Melinda J.; Iuga, Dinu; Gervais, Christel; Bonhomme, Christian
Abstract: 43 Ca nuclear magnetic resonance (NMR) spectroscopy has been extensively applied to the detailed study of octacalcium phosphate (OCP), Ca8 (HPO4 )2 (PO4 )4 .5H2 O, and hybrid derivatives involving intercalated metabolic acids (viz., citrate, succinate, formate, and adipate). Such phases are of importance in the development of a better understanding of bone structure. High‐resolution 43 Ca magic angle spinning (MAS) experiments, including double‐rotation (DOR) 43 Ca NMR, as well as 43 Ca{ 1 H} rotational echo DOR (REDOR) and 31 P{ 43 Ca} REAPDOR NMR spectra, were recorded on a 43 Ca‐labeled OCP phase at very high magnetic field (20 T), and complemented by ab initio calculations of NMR parameters using the Gauge‐Including Projector Augmented Wave–density functional theory (GIPAW‐DFT) method. This enabled a partial assignment of the eight inequivalent Ca 2+ sites of OCP. Natural‐abundance 43 Ca MAS NMR spectra were then recorded for the hybrid organic–inorganic derivatives, revealing changes in the 43 Ca lineshape. In the case of the citrate derivative, these could be interpreted on the basis of computational models of the structure. Overall, this study highlights the advantages of combining high‐resolution 43 Ca NMR experiments and computational modeling for studying complex hybrid biomaterials. Abstract : A combination of high‐field multinuclear NMR spectroscopy (including 43 Ca) and GIPAW DFT calculations was applied to characterize in depth octacalciumphosphate and its hybrid derivatives.